2009
DOI: 10.1093/jjco/hyp110
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Pathological Response of Prostate Cancer in a Patient with Metastatic Renal Cell Carcinoma on Sunitinib Treatment

Abstract: Sunitinib is a small molecular inhibitor of tyrosine kinases and is used to treat advanced renal cell carcinoma and gastrointestinal stromal tumour after disease progression or intolerance to imatinib therapy. Here, we describe biochemical and pathological response of prostate cancer in a patient with metastatic renal cell carcinoma during sunitinib treatment. A 62-year-old man was referred to our hospital because of a mass in the scalp. He was diagnosed with left renal cell carcinoma with right renal and scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Women were more represented with the 53.7% (66/123) of cases, compared to the 46.3% (57/123) of men . Median age of AN at onset was 59 (IQR: 47–68).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Women were more represented with the 53.7% (66/123) of cases, compared to the 46.3% (57/123) of men . Median age of AN at onset was 59 (IQR: 47–68).…”
Section: Resultsmentioning
confidence: 99%
“…According to gender distribution of primary tumours, we obviously found that the 100% of patients with uterus cancer (8/ 8) 64,65,84 while in 24.8% (30/121) cases, the diagnosis was synchronous. 7,8,18,20,23,31,33,35,44,46,48,56,68,69,72,73,[76][77][78]81,84,87,93,95,96,99,102,110,111 The specific sites of primary tumours in each of these subgroups were reported in Table S1 (Supporting Information). Considering cases diagnosed after the primary tumour, they were mainly derived from breast and GI cancers (18/88 cases each); synchronous cases prevalently had a GI origin (10/30 cases), while cases diagnosed before the primary tumour were only three (one from GI, namely one thyroid and one lung cancer).…”
Section: Demographic and Epidemiologic Datamentioning
confidence: 99%
See 3 more Smart Citations